The MITF regulatory network in melanoma - Chauhan, Jagat S.; Hölzel, Michael; Lambert, Jean‐Philippe; Buffa, Francesca M.; Goding, Colin R. (Pigment cell and melanoma research, 2022)
Bidirectional interactions between plastic tumor cells and the microenvironment critically impact tumor evolution and metastatic dissemination by enabling cancer cells to adapt to microenvironmental stresses by switching phenotype. In melanoma, a key determinant of phenotypic identity is the microphthalmia‐associated transcription factor MITF that promotes proliferation, suppresses senescence, and anticorrelates with immune infiltration and therapy resistance. What determines whether MITF can activate or repress genes associated with specific phenotypes, or how signaling regulating MITF might impact immune infiltration is poorly understood. Here, we find that MITF binding to genes associated with high MITF is via classical E/M‐box motifs, but genes downregulated when MITF is high contain FOS/JUN/AP1/ATF3 sites. Significantly, the repertoire of MITF‐interacting factors identified here includes JUN and ATF3 as well as many previously unidentified interactors. As high AP1 activity is a hallmark of MITFLow, invasive, slow‐cycling, therapy resistant cells, the ability of MITF to repress AP1‐regulated genes provides an insight into how MITF establishes and maintains a pro‐proliferative phenotype. Moreover, although β‐catenin has been linked to immune exclusion, many Hallmark β‐catenin signaling genes are associated with immune infiltration. Instead, low MITF together with Notch signaling is linked to immune infiltration in both mouse and human melanoma tumors.